Software-based method for automated intraoperative planning of Schoettle Point in surgical medial patellofemoral ligament reconstruction: a comparative validation study - Privalov, Maxim; Kordon, Florian; Kunze, Holger; Beisemann, Nils; Vetter, Sven Y.; Franke, Jochen; Grützner, Paul Alfred; Swartman, Benedict (The international journal of medical robotics and computer assisted surgery, 2024)
Background: The aim of the study was to validate a software-based planning method for the Schoettle Point and to evaluate precision and time efficiency of its live overlay on the intraoperative X-ray. Methods: A software-based method was compared with surgeons' manual planning in an inter- and intrarater study. Subsequently, K-wire placement was performed with and without an overlay of the planning. The time used and the precision achieved were statistically compared. Results: The average deviation between the surgeons (1.68 mm; 2.26 mm) was greater than the discrepancy between the surgeons and the software-based planning (1.30 mm; 1.38 mm). In the intrarater comparison, software-based planning provided consistent results. Live overlay showed a significantly lower positioning error (0.9 ± 0.5 mm) compared with that without overlay (3.0 ± 1.4 mm, p = 0.000; 3.1 ± 1.4 mm, p = 0.001). Live overlay did not achieve a significant time gain (p = 0.393; p = 0.678). Conclusion: The software-based planning and live overlay of the Schoettle Point improves surgical precision without negatively affecting time efficiency.
Vorab veröffentlicht: 04. Januar 2024
Gesehen am 27.03.2024